2022
DOI: 10.1136/rmdopen-2022-002626
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Disease Activity index for PSoriatic Arthritis (DAPSA) with a quick quantitative C reactive protein assay (Q-DAPSA) in patients with psoriatic arthritis: a prospective multicentre cross-sectional study

Abstract: ObjectivesThis study aimed to evaluate the Disease Activity index for PSoriatic Arthritis (DAPSA) based on a quick quantitative C reactive protein (qCRP) assay (Q-DAPSA) in a multicentre, prospective, cross-sectional study in patients with psoriatic arthritis (PsA).MethodsThe assessment of prospectively recruited study patients included joint examination and patient reported outcome (PRO) measures (patient global assessment, patient pain assessment). Following, the DAPSA based on a routine laboratory CRP measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(90 reference statements)
0
0
1
Order By: Relevance
“…Our study population was highly comparable to the general German PsA population reported from healthcare insurance data based on similar mean age (53.8 years in our study vs. 58.9 years) and similar proportions of females (55% vs. 63%) ( 26 ). Although DAPSA as a parameter of disease activity is not available for the general German PsA population, a smaller study (n=104) in German outpatients (with similar age and sex distribution) reported lower DAPSA mean (SD) scores of 10.5 (10.6) than observed here (17.9 [16.3]) ( 27 ). Given the high standard deviation for this parameter in both studies, this reported difference is likely not significant.…”
Section: Discussioncontrasting
confidence: 54%
“…Our study population was highly comparable to the general German PsA population reported from healthcare insurance data based on similar mean age (53.8 years in our study vs. 58.9 years) and similar proportions of females (55% vs. 63%) ( 26 ). Although DAPSA as a parameter of disease activity is not available for the general German PsA population, a smaller study (n=104) in German outpatients (with similar age and sex distribution) reported lower DAPSA mean (SD) scores of 10.5 (10.6) than observed here (17.9 [16.3]) ( 27 ). Given the high standard deviation for this parameter in both studies, this reported difference is likely not significant.…”
Section: Discussioncontrasting
confidence: 54%